Methodological Design of Risk Management and Social Responsibility in The School of Engineering of a Peruvian University - Acevedo, Jesús Enrique Reyes; Legoas, Rosa Maria Velarde; Torres, Yuli Novak Ormeño; Medina, Jorge Lázaro Franco; Robles, Roberto Alejandro Pacheco; Panduro, Walker Diaz; Gonzales, Jose Humberto Meneses (International Journal of Membrane Science and Technology, 2023)
The objective of this study is to design the Risk Management methodology for the University Social Responsibility (USR) process, with the participation of the administrative and teaching staff of the Mechanical and Electrical Engineering School of a private Peruvian university as a contribution to the licensing project in 2021. The population consisted of 38 people involved in the USR process in the University’s Mechanical and Electrical Engineering PE, including teaching and administrative staff. The methodology uses a mixed approach, explanatory scope and sequential explanatory design (DEXPLIS). Although very few universities apply risk management at the institutional level, the results show that it is feasible to design a risk management methodology applied to a specific educational management process that contributes to achieving institutional objectives. Therefore, it is concluded that the successful design of a risk management methodology facilitates the achievement of the objectives of the process to which risk management is applied and that risk management can have a direct impact on the licensing process by aligning the USR sub-processes with the sub-processes and indicators of the licensing process, being essential for a good design not only to know the dimensions of risk management but also to know the process applied, in this case, the process of University Social Responsibility.